If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-2) + -1y = -2 Multiply 3 * -2 -6 + -1y = -2 Solving -6 + -1y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1y = -2 + 6 Combine like terms: -6 + 6 = 0 0 + -1y = -2 + 6 -1y = -2 + 6 Combine like terms: -2 + 6 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4
| x^4-x^2+6*x-20=0 | | 3x-(-1)=-2 | | 25-1/4x^2=0 | | x^3+2x^2-4x-4=0 | | 25r-12=3 | | -4+11(3-a)=29-11a | | t+3t-7=12 | | 10/5-10/5 | | 2x-1/x-2-4 | | (x^2-6x)=(10-3x) | | 0.25x^2+1=-0.5x^2+2x+0.5 | | 2/9*45 | | 8x+4y+9z-4x=5z-6y | | 3y-1.8-4-3x=7x-6 | | 2(3x-5)(8-x)=0 | | 2x/2x^2 | | y=-1.75x+5 | | 3(2p+7)=5(p-4) | | x(6-x)=7 | | 11*x=43-2*x | | (2/5X)/(6X/7)= | | 2x-(100-x)=0 | | f(-1)=x^2+6x-11 | | f(-4)=x^2+6x-11 | | 1/(x-2)-1/(x-1)=1/6 | | 7X/10=5/10 | | 1.71=x^5 | | 2x^2-10x+8=2(x-1)(x-4) | | 5x-9=5+5c | | 5x+9=5+5c | | 4t+3= | | P/4-6/6=-8 |